Call for Asymmetric Health Decentralisation in Indonesia - Nugroho, Arief Priyo; Handayani, Sri (Pusjar SKPP Lembaga Administrasi Negara, 2022)
Disparities, Inequalities and inequities are still significant problems after decades of experiencing health decentralisation. This study arranges massive issues on health decentralisation to endorse improvement. The analysis offers insight into decentralisation practices in Indonesia to perform health affairs. A systematic review approach was practised to identify the Scopus database and PubMed MEDLINE from 1999 to 2020, using the terms